Ответы и объяснения

2012-09-27T20:37:16+04:00

х^4+12х^2=16-3х^2

x^4+12x^2+3x^2-16=0

x^4+15x^2-16=0

пусть t=x^2 ,тогда

t^2+15t-16=0

D=225*(-4)*1*(-16)=225+64=289=17^2

t1=-32|2=-16(не подходит)

t2=2/2=1

т.к t2=x^2,то х2^2=1;-1

ответ -1;1

2012-09-27T20:38:13+04:00

x^4+12x^2=16-3x^2
x^2=x
x^2+12x=16-3x

x^2+12x+3x-16=0
x^2+15x-16=0
D=b^2-4ac=225+64=289
x1=\frac{-b-\sqrt{D}}{2a} =\frac{-15-17}{2}=\frac{-32}{2}=-16
x2= \frac{-b+\sqrt{D}}{2a}=\frac{-15+17}{2}=1
-16 не подходит т.к -16^2\neq -16
а 1^2=1
ответ:х=1